(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
The right to information gives a fundamental right under Article 19 (1) of the Indian Constitution. The Supreme Court held that in Indian democracy, people are the masters and they have the right to know about the working of the government. Thus the government enacted the Right to Information act in 2005 which provides machinery for exercising this fundamental right. The Right to Information (RTI) Act 2005 was published in the Gazette of India on 21 June 2005. The aim of the Act is to provide for setting out the practical regime of right to information for citizens to secure access to information under the control of public authorities, in order to promote transparency and accountability in the working of every public authority. The Act provides a powerful tool to common citizens of India to seek information from public authorities. The public authorities now require maintaining transparency and will be held accountable. Medico-legal work, particularly autopsy is a confidential work; and the Act creates constrains whether information should be given or denied. We examined all available applications filed under the Right to Information Act 2005 through 2009 to 2021. A standard format was designed to collect the information to ensure consistency for the whole sample. Only application related to postmortem examinations were included in the study. Information collected included the nature of information sought, number of questions, whether the applicant belonged to below poverty line. Mode of receipt of information was needed by hand or through post, purpose of seeking information, any relation with the deceased and whether applicant had filed first appeal to the First appellate authority.